Editorial. Issue 1 (January 2018) - Mansfield-Devine, Steve
Abstract : The true seriousness of the Meltdown and Spectre bugs (see main news story) will only become apparent over time. We don't yet know how exploitable these flaws are outside of the laboratory, or whether malicious actors will be able to take advantage of them.